Sulfur-tolerant Fe-based CO oxidation catalyst as well as preparation method and application thereof
By pre-reduction and inducing activation preparation of the catalyst parent body, a specific surface-interface structure is formed, which solves the problem of difficult to deal with sulfur-containing CO exhaust gas in the prior art, and achieves an efficient and stable CO conversion effect.
Patent Information
- Application Number
- CN202311166880.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The prior art is difficult to effectively treat exhaust gases containing low concentrations of CO, especially in the presence of sulfides, noble metal catalysts are prone to deactivate, and sulfur-resistant catalysts are rarely reported.
Pre-reduction-induced activation of the catalyst parent body is prepared to form a Fe/FeOx/MOx surface-interface structure, so that the catalyst has a selective oxidation function and improves sulfur resistance.
The efficient CO conversion rate in the presence of sulfide is achieved. The CO conversion rate of the catalyst remains above 99% after 300h reaction time, and the composition is simple and the preparation cost is low, making it suitable for large-scale production.
Smart Images

Figure CN119588354A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon monoxide oxidation catalysts, and in particular to a sulfur-resistant Fe-based CO oxidation catalyst and a preparation method and application thereof. Background Art
[0002] Carbon monoxide (CO) is a colorless, odorless, toxic gas that generally comes from incomplete combustion or partial oxidation of coal, gasoline and natural gas. CO has a strong binding force with hemoglobin and is therefore highly toxic. At higher concentrations, it can cause varying degrees of poisoning symptoms in people, harming the brain, heart, liver, kidney, lungs and other tissues of the human body, and even electric shock-like death. The minimum lethal concentration for human inhalation is 5000ppm (5 minutes). Therefore, in the production process of petrochemical products, strict requirements should be made for the emission content of CO in tail gas. With increasingly stringent environmental protection requirements, Beijing, Zibo and other regions have strictly restricted the CO concentration in the tail gas of chemical plants.
[0003] In some chemical production processes, the tail gas produced contains low concentration of CO gas (<20000ppm) (such as the analytical gas and CO2 product gas of the low-temperature methanol washing device used for acid gas removal in the coal gasification unit). For this type of tail gas, the recovery cost is relatively high. In order to meet the emission requirements, adsorption, photocatalysis, low-temperature plasma conversion, combustion and other methods are usually used to remove CO. Among them, the catalytic oxidation method introduces a high-efficiency catalyst on the basis of the combustion method to reduce the temperature of the combustion process. It has the advantages of simple process and high removal efficiency, and therefore has received widespread attention.
[0004] At present, there are many public reports on catalysts for the catalytic oxidation of low-concentration CO, usually using precious metals such as Pt and Au as active components. However, CO-containing exhaust gases from many chemical plants usually contain low concentrations of sulfides (<50ppm, including H2S, COS, etc.) due to the influence of previous processes. Such sulfur-containing compounds have a strong poisoning effect on precious metal catalysts and can easily lead to catalyst deactivation. At present, there are few reports on sulfur-resistant carbon monoxide oxidation catalysts, and the few catalysts that can be used for the treatment of sulfur-containing CO tail gas usually require more stringent reaction conditions.
[0005] Patent application CN114210335A discloses the preparation and application of a low-temperature, water-resistant and sulfur-resistant non-precious metal catalyst for removing carbon monoxide. The catalyst is a perovskite-type transition metal oxide (general formula: La 1 x Sr x CoO3). The catalyst can achieve 0 1000mg Nm 3 10000ppm CO flue gas of SO2 and 0-20vol.% water vapor at 120150℃ and 3000-30000h1 Under the conditions of space velocity, the efficiency of removing carbon monoxide is stable at more than 80%, but the activity and stability of the catalyst in the presence of other sulfur species such as H2S are not indicated.
[0006] Patent application CN111659415A discloses a method for preparing a coupled nanocomposite noble metal catalyst on an activated alumina carrier. The catalyst uses activated alumina as a carrier, CeO2, Fe3O4, MnO2, CuO2 coupled metal oxides as modification aids, and Pd and Pt dual noble metals as active components. At 25°C, when the CO inlet concentration is 5000ppm, the H2S content is 5ppm, and the air velocity is 10000h -1 Under the condition of 50h reaction time, the CO removal rate is maintained at 100%. However, the catalyst composition is complex and the preparation method is relatively cumbersome. At the same time, the change of hydrogen sulfide during the reaction is not mentioned, and the life of the catalyst cannot be further speculated. The reported catalyst life is far from industrial application.
[0007] Therefore, in view of the characteristics of sulfur-containing species in CO tail gas of the petrochemical industry, the targeted development of CO oxidation catalysts with intrinsic sulfur resistance has become a difficult problem that needs to be solved urgently. Summary of the invention
[0008] The purpose of the present invention is to provide a sulfur-resistant Fe-based CO oxidation catalyst and its preparation method and application for improving the catalytic stability of the catalyst in the presence of sulfides (hydrogen sulfide, etc.) in the tail gas treatment process containing low concentration CO in industrial production processes including coal chemical industry. The sulfur-resistant Fe-based CO oxidation catalyst of the present invention is prepared by pre-reduction-induced activation of the catalyst matrix to form a specific surface-interface structure, so that the catalyst can realize the selective oxidation function of sulfur-containing species and obtain excellent sulfur-resistant reaction ability in the carbon monoxide oxidation reaction.
[0009] In order to achieve the above object, the present invention provides a sulfur-resistant Fe-based CO oxidation catalyst, which comprises a carrier and an active component supported on the carrier, wherein the active component is Fe, the carrier is at least one of alumina, titanium dioxide, cerium dioxide and zirconium dioxide, and the sulfur-resistant Fe-based CO oxidation catalyst forms Fe / FeO x / MO x Surface-interface structure, where Fe is in a sulfur-hybridized state, FeO x is iron oxide, MO x As a carrier.
[0010] Preferably, based on the total weight of the sulfur-resistant Fe-based CO oxidation catalyst, the loading amount of the active component in terms of metal element is 2-10 wt %.
[0011] The present invention also provides a method for preparing a sulfur-resistant Fe-based CO oxidation catalyst, the method comprising the following steps:
[0012] (1) impregnating the support into an aqueous solution of an iron precursor, and then drying and calcining the solution to obtain a catalyst matrix;
[0013] (2) subjecting the catalyst precursor to a pre-reduction treatment in a hydrogen-containing atmosphere to obtain a catalyst intermediate;
[0014] (3) inducing activation of the catalyst intermediate in an atmosphere containing CO and H2S;
[0015] Wherein, the carrier is at least one of alumina, titania, cerium dioxide and zirconium dioxide.
[0016] Preferably, in step (1), the impregnation process is equal volume impregnation.
[0017] Preferably, the impregnation process includes a stirring stage and a standing stage, the stirring stage lasts for 0.5-1 h, and the standing stage lasts for 6-18 h.
[0018] Preferably, in step (1), the carrier is calcined before impregnation.
[0019] Preferably, the calcination conditions of the carrier include: a temperature of 400-700° C. and a calcination time of 4-8 hours.
[0020] Preferably, the particle size of the carrier is 10-500 nm and the specific surface area is 60-200 m 2 / g.
[0021] Preferably, in step (1), the iron precursor is at least one of iron nitrate, iron chloride and iron sulfate, preferably iron nitrate.
[0022] Preferably, in step (1), during the drying process, the drying temperature is 60-90°C, and the drying time is 12-24h; during the roasting process, the roasting temperature is 400-600°C, the roasting time is 3-6h, and the heating rate is 1-3°C / min.
[0023] Preferably, in step (2), the hydrogen content in the atmosphere of the pre-reduction treatment is 5-50% by volume, preferably 5-10% by volume.
[0024] Preferably, the temperature of the pre-reduction treatment is 300-500°C.
[0025] Preferably, in step (3), the activation-inducing atmosphere contains CO, H2S and N2, wherein the CO content is 2-5% by volume, the H2S content is 50-200 ppm, and the N2 content is 95-98% by volume.
[0026] Preferably, the activation induction temperature is 200-350°C.
[0027] The present invention also provides a sulfur-resistant Fe-based CO oxidation catalyst prepared by the method.
[0028] The present invention also provides the use of the above sulfur-resistant Fe-based CO oxidation catalyst as a catalyst for carbon monoxide oxidation reaction.
[0029] Preferably, the reaction raw gas used in the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
[0030] The technical solution of the present invention has the following advantages:
[0031] (1) Compared with other carbon monoxide oxidation catalysts, the sulfur-resistant Fe-based CO oxidation catalyst of the present invention can achieve highly selective oxidation of hydrogen sulfide species to sulfur dioxide, reducing the adsorption and deposition of sulfur species on the catalyst;
[0032] (2) Compared with other carbon monoxide oxidation catalysts, the sulfur-resistant Fe-based CO oxidation catalyst of the present invention has a high efficiency at a space velocity of 10000 h -1 , reaction temperature 350°C, inlet CO concentration 6000ppm and the presence of 50ppm hydrogen sulfide, after 300h reaction time, the CO conversion rate still remained above 99%.
[0033] The composition and preparation method of the sulfur-resistant Fe-based CO oxidation catalyst of the present invention are simple, the preparation cost is low, the repeatability is good, it is suitable for large-scale production, and its activity is efficient and stable. Relying on the catalyst of the present invention, a low-concentration carbon monoxide catalytic removal technology can be formed, which is suitable for a variety of low-concentration carbon monoxide removal conditions including the presence of sulfides, and can reduce the carbon monoxide concentration in the tail gas to below 50ppm. It can be widely used in tail gas treatment in petrochemical, steel, industrial kilns, garbage incineration and other processes, and is of great significance for protecting the atmospheric environment and ensuring human health. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a graph of CO conversion rate of Fe / TiO2 catalytic oxidation in Example 1;
[0035] Figure 2 This is the TEM image of the catalyst Fe / TiO2 in Example 1. DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0037] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0038] Unless otherwise specified, the mass percentage of each component constituting the catalyst in the present application refers to the mass percentage of the corresponding component in the mass of the catalyst.
[0039] Unless otherwise specified, the content of each component in the gas composition used for catalyst pre-reduction and induced activation in this application refers to the volume percentage of the corresponding component in the total gas volume.
[0040] The sulfur-resistant Fe-based CO oxidation catalyst of the present invention comprises a carrier and an active component supported on the carrier. The active component is Fe, wherein the Fe may exist in the form of metal, oxide or a combination thereof. The carrier is at least one of alumina, titanium dioxide, cerium dioxide and zirconium dioxide.
[0041] In the catalyst of the present invention, the catalyst is prepared by equal volume impregnation-drying-calcination-prereduction-induced activation, the catalyst has good active component dispersion, and forms Fe / FeO x / MO x Surface-interface structure, where Fe is in a sulfur-hybridized state, FeO x It is iron oxide (such as Fe2O3, FeO, Fe3O4, etc.), MO x As carrier (MO x is TiO2, ZrO2, CeO2 or Al2O3).
[0042] In the catalyst of the present invention, based on the total weight of the sulfur-resistant Fe-based CO oxidation catalyst, the loading amount of the active component in terms of metal element is 2-10wt%, preferably 3-8wt%, and more preferably 6-8wt%.
[0043] The method for preparing the sulfur-resistant Fe-based CO oxidation catalyst of the present invention comprises the following steps:
[0044] (1) impregnating the support into an aqueous solution of an iron precursor, and then drying and calcining the solution to obtain a catalyst matrix;
[0045] (2) subjecting the catalyst precursor to a pre-reduction treatment in a hydrogen-containing atmosphere to obtain a catalyst intermediate;
[0046] (3) Inducing activation of the catalyst intermediate in an atmosphere containing CO and H2S.
[0047] In the method of the present invention, the carrier is at least one of alumina, titanium dioxide, cerium dioxide and zirconium dioxide. The particle size of the carrier can be 10-500nm, and the specific surface area can be 60-200m 2 In one embodiment, when the carrier is titanium dioxide, it is preferably anatase-type nano-titanium dioxide white powder with a purity of more than 99.9%, a particle size of 15-60 nm, and a specific surface area of 60-120 m 2 / g, the carrier has a large specific surface area and good hydrophilicity. In another embodiment, when the carrier is cerium dioxide, zirconium dioxide or aluminum oxide, its purity is preferably above 99.99%.
[0048] In the method of the present invention, the carrier is calcined before impregnation. The calcination conditions of the carrier may include: a temperature of 400-700° C. and a calcination time of 4-8 hours.
[0049] In the method of the present invention, the iron precursor is at least one of iron nitrate, chloride and sulfate, preferably iron nitrate.
[0050] In the method of the present invention, in step (1), the impregnation process is preferably equal volume impregnation. The specific operation process of the equal volume impregnation includes:
[0051] (I) The calcined carrier is subjected to a carrier saturated water absorption test, and the specific method is as follows: weigh a certain mass m1 of the carrier and put it into a measuring cylinder to obtain its dense volume V1; add a certain mass m2 of deionized water and record its volume V2; after sufficient stirring and standing for 12-24 hours, read the volume V3 of the mixed solution in the measuring cylinder, and the saturated water absorption rate ω of the sample is calculated by the following formula:
[0052]
[0053] (II) calculating the weight of the iron precursor according to the mass of the carrier required for preparing the catalyst, dissolving the iron precursor calculated according to the loading amount in deionized water, the volume of deionized water required for dissolution being obtained according to the saturated water absorption calculated according to the weight of the carrier for preparing the catalyst, and allowing the clarified precursor solution to stand for use;
[0054] (III) adding the calcined carrier to the prepared precursor solution, allowing the carrier to fully absorb the precursor solution, stirring for a period of time at room temperature to obtain a slurry mixture, and then letting it stand for a period of time.
[0055] Wherein, the impregnation process of step (III) includes a stirring stage and a standing stage, the stirring stage lasts for 0.5-1 h, and the standing stage lasts for 6-18 h.
[0056] In the method of the present invention, in step (1), during the drying process, the drying temperature is 60-90° C. and the drying time is 12-24 hours. The drying process can be carried out in a blast drying oven.
[0057] In the method of the present invention, in step (1), during the calcination process, the calcination temperature is 400-600° C., the calcination time is 3-6 hours, and the heating rate is 1-3° C. / min. The calcination process can be carried out in a muffle furnace.
[0058] In the method of the present invention, in step (2), the content of hydrogen in the atmosphere of the pre-reduction treatment is 5-50% by volume, preferably 5-20% by volume, and more preferably 5-10% by volume. In addition to hydrogen, other gases in the atmosphere of the pre-reduction treatment may be inert gases, such as argon.
[0059] In the method of the present invention, in step (2), the temperature of the pre-reduction treatment is 300-500° C. The time of the pre-reduction treatment can be 0.5-2 hours, preferably 1 hour.
[0060] In the method described in the present invention, in step (3), during the induction activation process, the catalyst structure undergoes a directional change, the H2S component in the reaction gas is selectively oxidized to SO2, and as the induction time increases, the SO2 concentration in the tail gas gradually increases, and after a period of induction time, the sulfur concentration in and out of the reactor reaches equilibrium, and the sulfur species will not continue to deposit on the catalyst. During the catalyst induction activation process, the CO oxidation reaction conversion rate is always maintained at more than 99%, so an intrinsic sulfur-resistant reaction can be achieved. Depending on the composition of the catalyst and the composition of the reaction induction gas, the induction period required from the start of reaction induction to the sulfur balance between the reactor inlet and outlet is different, and the induction time is 10-18h. In a preferred case, the induction activation atmosphere contains CO, H2S and N2, wherein the CO content is 2-5% by volume, the H2S content is 50-200ppm, and the N2 content is 95-98% by volume.
[0061] In the method of the present invention, in step (3), the temperature for inducing activation is 200-350°C.
[0062] According to a specific embodiment of the present invention, the method for preparing the sulfur-resistant Fe-based CO oxidation catalyst comprises:
[0063] S1, adding the calcined carrier to the prepared iron precursor solution, allowing the carrier to fully absorb the precursor solution, stirring and mixing at room temperature, and then standing to obtain a slurry mixture;
[0064] S2, placing the slurry mixture in a forced air drying oven for drying, and then placing it in a muffle furnace for calcination to obtain a catalyst matrix;
[0065] S3. The catalyst precursor is placed in a flowing fixed bed reactor, firstly subjected to a pre-reduction treatment in a H2 / Ar mixed gas atmosphere, and then the gas is switched to a CO / H2S / N2 mixed gas, and induced activation is performed in the mixed gas atmosphere.
[0066] The present invention also provides a sulfur-resistant Fe-based CO oxidation catalyst prepared by the above method. In the present invention, by pre-reducing and inducing activation of the catalyst matrix, a specific catalytic active site and surface-interface structure are formed, a highly selective oxidation process of H2S species can be achieved, the adsorption of S species and the sulfate formation process are suppressed, and a high conversion rate oxidation reaction of carbon monoxide in the presence of H2S is achieved.
[0067] The present invention also provides the use of the above-mentioned sulfur-resistant Fe-based CO oxidation catalyst as a catalyst for carbon monoxide oxidation reaction. Specifically, the sulfur-resistant Fe-based CO oxidation catalyst described in the present invention can be applied to a variety of low-concentration carbon monoxide removal conditions, especially a variety of low-concentration carbon monoxide removal conditions in the presence of sulfides. In a specific embodiment, the reaction raw gas used in the process of the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
[0068] Relying on the catalyst described in the present invention, a low-concentration carbon monoxide catalytic removal technology can be formed, which is suitable for a variety of low-concentration carbon monoxide removal conditions including the presence of sulfides, and can reduce the carbon monoxide concentration in the exhaust gas to below 50ppm. It can be widely used in exhaust gas treatment in petrochemical, steel, industrial kilns, waste incineration and other processes, and is of great significance for protecting the atmospheric environment and ensuring human health.
[0069] The following examples further illustrate the sulfur-resistant Fe-based CO oxidation catalyst and its preparation method and application according to the present invention. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0070] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0071] Example 1
[0072] Preparation of intrinsically sulfur-resistant Fe / TiO2 catalyst:
[0073] The commercial anatase nano-titanium dioxide carrier (purity of more than 99.9%, particle size of 15-60nm, specific surface area of 60-120m 2 / g), placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours with a heating rate of 3°C / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0074] Determination of saturated water absorption rate: Weigh 1g of calcined TiO2 carrier, add it to a 5mL measuring cylinder, tap it on a flat surface, and read the dense volume as 1mL. Add 2mL of water, stir it thoroughly, and let it stand for 12h. Read the volume of the mixed solution as 2.3mL. The saturated water absorption rate of the TiO2 carrier is calculated to be 0.7mL / g.
[0075] Weigh 3.79g of ferric nitrate (Fe(NO3)3·9H2O) into a 50mL beaker, add 6.3mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of TiO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0076] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 4 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0077] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 500°C for 1h in a 100mL / min 10vol% H2 / 90vol% Ar mixed gas atmosphere. The gas was then switched to a 2vol% CO / 0.005vol% H2S / 97.995vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results of the CO conversion rate of the Fe / TiO2 catalyst catalytic oxidation are as follows: Figure 1 As shown, from Figure 1 It can be seen that during the 200h long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate is maintained above 99%.
[0078] The ICP-OES characterization method detected that in the catalyst Fe / TiO2, based on its total weight, the content of Fe in terms of metal element is 7.98% by weight.
[0079] The transmission electron microscope (TEM) spectrum characterization (TEM) of the Fe / TiO2 catalyst obtained after induced activation is shown in the figure below: Figure 2 shown.
[0080] The results of high-foot annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / TiO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0081] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a unique Fe / Fe2O3 / TiO2 surface-interface structure was formed on the Fe / TiO2 catalyst, which is beneficial to improving the catalytic reaction activity and stability.
[0082] Example 2
[0083] Preparation of intrinsically sulfur-resistant Fe / ZrO2 catalyst:
[0084] The nano zirconium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours with a heating rate of 3°C / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0085] Determination of saturated water absorption rate: Weigh 1g of calcined ZrO2 carrier, add it to a 5mL measuring cylinder, and knock it on a flat surface. The dense volume is 0.65mL. After adding 2mL of water, stir it thoroughly and let it stand for 12h. The volume of the mixed solution is 2.3mL. The saturated water absorption rate of the ZrO2 carrier is calculated to be 0.35mL / g.
[0086] Weigh 3.79g of ferric nitrate (Fe(NO3)3·9H2O) into a 50mL beaker, add 3.2mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of ZrO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0087] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 4 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0088] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 500°C for 1h in a 100mL / min 10vol% H2 / 90vol% Ar mixed gas atmosphere. The gas was then switched to a 2.5vol% CO / 0.01vol% H2S / 97.49vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 14 hours. During the 300-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0089] The ICP-OES characterization method detected that in the catalyst Fe / ZrO2, based on the total weight, the content of Fe in terms of metal element is 7.02% by weight.
[0090] The results of high-legged annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / ZrO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0091] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a unique Fe / Fe2O3 / ZrO2 surface-interface structure was formed on the Fe / ZrO2 catalyst.
[0092] Example 3
[0093] Preparation of intrinsically sulfur-resistant Fe / CeO2 catalyst:
[0094] The nano-cerium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours with a heating rate of 3°C / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0095] Determination of saturated water absorption rate: Weigh 1g of calcined CeO2 carrier, add it to a 5mL measuring cylinder, and knock it on a flat surface. The dense volume is 0.8mL. After adding 2mL of water, stir it thoroughly and let it stand for 12h. The volume of the mixed solution is 2.2mL. The saturated water absorption rate of the CeO2 carrier is calculated to be 0.6mL / g.
[0096] Weigh 3.79g of ferric nitrate (Fe(NO3)3·9H2O) and add them to a 50mL beaker. Add 3.2mL of deionized water and stir thoroughly to dissolve. Then, add 10g of CeO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0097] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 4 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0098] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 500°C for 1h in a 100mL / min 5vol% H2 / 95vol% Ar mixed gas atmosphere. The gas was then switched to a 5vol% CO / 0.02vol% H2S / 94.98vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 17.5 hours. During the 300-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0099] The ICP-OES characterization method detected that in the catalyst Fe / CeO2, based on the total weight, the content of Fe in terms of metal element is 7.56% by weight.
[0100] The results of high-foot annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / CeO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0101] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a unique Fe / Fe2O3 / CeO2 surface-interface structure was formed on the Fe / CeO2 catalyst, which is beneficial to improving the catalytic reaction activity and stability.
[0102] Example 4
[0103] Preparation of intrinsically sulfur-resistant Fe / TiO2 catalyst:
[0104] The commercial anatase nano-titanium dioxide carrier (purity of more than 99.9%, particle size of 15-60nm, specific surface area of 60-120m 2 / g), placed in a muffle furnace, and calcined at 400°C in air atmosphere for 8 hours, with a heating rate of 1°C / min. After the calcination is completed, it is naturally cooled to room temperature and sealed for storage.
[0105] Determination of saturated water absorption rate: Weigh 1g of calcined TiO2 carrier, add it to a 5mL measuring cylinder, tap it on a flat surface, and read the dense volume as 1mL. Add 2mL of water, stir it thoroughly, and let it stand for 12h. Read the volume of the mixed solution as 2.3mL. The saturated water absorption rate of the TiO2 carrier is calculated to be 0.7mL / g.
[0106] Weigh 3.39g of ferric nitrate (Fe(NO3)3·9H2O) into a 50mL beaker, add 6.3mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of TiO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0107] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 400°C at a heating rate of 1°C / min, and calcined at 400°C for 6 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0108] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 400°C for 1h in a 100mL / min 10vol% H2 / 90vol% Ar mixed gas atmosphere. The gas was then switched to a 2vol% CO / 0.005vol% H2S / 97.995vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 15 hours. During the 300-hour long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0109] The ICP-OES characterization method detected that in the catalyst Fe / TiO2, based on its total weight, the content of Fe in terms of metal element is 7.13% by weight.
[0110] The results of high-foot annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / TiO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0111] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a Fe / Fe2O3 / TiO2 surface-interface structure was formed on the Fe / TiO2 catalyst.
[0112] Example 5
[0113] Preparation of intrinsically sulfur-resistant Fe / TiO2 catalyst:
[0114] The commercial anatase nano-titanium dioxide carrier (purity of more than 99.9%, particle size of 15-60nm, specific surface area of 60-120m 2 / g), placed in a muffle furnace, and calcined at 700℃ in air atmosphere for 4h, with a heating rate of 2℃ / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0115] Determination of saturated water absorption rate: Weigh 1g of calcined TiO2 carrier, add it to a 5mL measuring cylinder, tap it on a flat surface, and read the dense volume as 1mL. Add 2mL of water, stir it thoroughly, and let it stand for 12h. Read the volume of the mixed solution as 2.3mL. The saturated water absorption rate of the TiO2 carrier is calculated to be 0.7mL / g.
[0116] Weigh 2.89g of ferric nitrate (Fe(NO3)3·9H2O) into a 50mL beaker, add 6.3mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of TiO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0117] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 600°C at a heating rate of 3°C / min, and calcined at 600°C for 3 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0118] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 450°C for 1h in a 100mL / min 10vol% H2 / 90vol% Ar mixed gas atmosphere. The gas was then switched to a 2vol% CO / 0.005vol% H2S / 97.995vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 16 hours. During the 300-hour long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0119] The ICP-OES characterization method detected that in the catalyst Fe / TiO2, based on its total weight, the content of Fe in terms of metal element is 6.09 weight %.
[0120] The results of high-foot annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / TiO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0121] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a Fe / Fe2O3 / TiO2 surface-interface structure was formed on the Fe / TiO2 catalyst.
[0122] Example 6
[0123] Preparation of intrinsically sulfur-resistant Fe / ZrO2 catalyst:
[0124] The nano zirconium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 400°C in air atmosphere for 8 hours, with a heating rate of 1°C / min. After the calcination is completed, it is naturally cooled to room temperature and sealed for storage.
[0125] Determination of saturated water absorption rate: Weigh 1g of calcined ZrO2 carrier, add it to a 5mL measuring cylinder, and knock it on a flat surface. The dense volume is 0.65mL. After adding 2mL of water, stir it thoroughly and let it stand for 12h. The volume of the mixed solution is 2.3mL. The saturated water absorption rate of the ZrO2 carrier is calculated to be 0.35mL / g.
[0126] Weigh 4.13g of ferric nitrate (Fe(NO3)3·9H2O) into a 50mL beaker, add 3.2mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of ZrO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0127] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 400°C at a heating rate of 1°C / min, and calcined at 400°C for 6 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0128] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 400°C for 1h in a 100mL / min 10vol% H2 / 90vol% Ar mixed gas atmosphere. The gas was then switched to a 2.5vol% CO / 0.01vol% H2S / 97.49vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 14 hours. During the 300-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0129] The ICP-OES characterization method detected that in the catalyst Fe / ZrO2, based on the total weight, the content of Fe in terms of metal element is 7.65% by weight.
[0130] The results of high-legged annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / ZrO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0131] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a unique Fe / Fe2O3 / ZrO2 surface-interface structure was formed on the Fe / ZrO2 catalyst.
[0132] Example 7
[0133] Preparation of intrinsically sulfur-resistant Fe / ZrO2 catalyst:
[0134] The nano zirconium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 700℃ in air atmosphere for 4h, with a heating rate of 2℃ / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0135] Determination of saturated water absorption rate: Weigh 1g of calcined ZrO2 carrier, add it to a 5mL measuring cylinder, and knock it on a flat surface. The dense volume is 0.65mL. After adding 2mL of water, stir it thoroughly and let it stand for 12h. The volume of the mixed solution is 2.3mL. The saturated water absorption rate of the ZrO2 carrier is calculated to be 0.35mL / g.
[0136] Weigh 3.49g of ferric nitrate (Fe(NO3)3·9H2O) into a 50mL beaker, add 3.2mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of ZrO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0137] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 600°C at a heating rate of 3°C / min, and calcined at 600°C for 3 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0138] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 450°C for 1h in a 100mL / min 10vol% H2 / 90vol% Ar mixed gas atmosphere. The gas was then switched to a 2.5vol% CO / 0.01vol% H2S / 97.49vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 14 hours. During the 300-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0139] The ICP-OES characterization method detected that in the catalyst Fe / ZrO2, based on its total weight, the content of Fe in terms of metal element is 6.48% by weight.
[0140] The results of high-legged annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / ZrO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0141] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a unique Fe / Fe2O3 / ZrO2 surface-interface structure was formed on the Fe / ZrO2 catalyst.
[0142] Example 8
[0143] Preparation of intrinsically sulfur-resistant Fe / CeO2 catalyst:
[0144] The nano-cerium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 600℃ in air atmosphere for 4h, with a heating rate of 3℃ / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0145] Determination of saturated water absorption rate: Weigh 1g of calcined CeO2 carrier, add it to a 5mL measuring cylinder, and knock it on a flat surface. The dense volume is 0.8mL. After adding 2mL of water, stir it thoroughly and let it stand for 12h. The volume of the mixed solution is 2.2mL. The saturated water absorption rate of the CeO2 carrier is calculated to be 0.6mL / g.
[0146] Weigh 3.42g of ferric nitrate (Fe(NO3)3·9H2O) and add them to a 50mL beaker. Add 3.2mL of deionized water and stir thoroughly to dissolve. Then, add 10g of CeO2 carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with sealing film. Place in a cool and dry place and let stand for 12h.
[0147] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 600°C at a heating rate of 3°C / min, and calcined at 600°C for 3 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0148] The prepared catalyst matrix was placed in a fixed bed microreactor and pretreated at 450°C for 1h in a 100mL / min 5vol% H2 / 95vol% Ar mixed gas atmosphere. The gas was then switched to a 5vol% CO / 0.02vol% H2S / 94.98vol% N2 mixed gas for induced activation. During the induced activation process, a gas chromatograph was used to analyze the sulfide content in the tail gas at the reactor outlet. When the sulfide content in the tail gas was the same as the sulfur content in the induced gas, the induced activation was considered complete. The gas was then switched to 0.6vol% CO / 0.005vol% H2S / 5vol% O2 / N2 gas for carbon monoxide oxidation reaction evaluation. The reaction temperature was set to 350°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 17.5 hours. During the 300-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0149] The ICP-OES characterization method detected that in the catalyst Fe / CeO2, based on the total weight, the content of Fe in terms of metal element is 6.83% by weight.
[0150] The results of high-foot annular dark field scanning transmission electron microscopy (STEM-HAADF) show that Fe in the Fe / CeO2 catalyst exists in the form of metal and oxide, and the Fe species after induced activation is in a sulfur-hybridized state.
[0151] High-resolution transmission electron microscopy (HRTEM) revealed that after induced activation, a Fe / Fe2O3 / CeO2 surface-interface structure was formed on the Fe / CeO2 catalyst.
[0152] Comparative Examples 1-3
[0153] The preparation methods of Comparative Examples 1, 2, and 3 correspond to those of Examples 1, 2, and 3, respectively, but the difference is that in the catalyst preparation process of Comparative Examples 1-3, the steps of pre-reduction treatment and induced activation are eliminated, and the calcined catalyst matrix is directly subjected to carbon monoxide oxidation reaction evaluation in 0.6 vol% CO / 0.005 vol% H2S / 5 vol% O2 / N2 gas. The reaction temperature is set to 350°C and the reaction space velocity is 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The activity and stability of each example and comparative example are shown in Table 1.
[0154] It can be seen from the analysis of high-foot annular dark field scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) that the catalysts prepared in the above comparative examples 1-3 do not contain any sulfidized Fe species or Fe / FeO x / MO x Surface-interface structure.
[0155] The comparison of the reaction activity evaluation of Examples 1-8 and Comparative Examples 1-3 is shown in Table 1, wherein T50 and T90 refer to the lowest temperatures at which the conversion rate reaches 50% and 90%, respectively.
[0156] Table 1
[0157]
[0158] It can be seen from the results of the above examples and comparative examples that the catalyst activity and stability of the sulfur-resistant Fe-based CO oxidation catalyst prepared by the method of the present invention are significantly better than those of the catalyst prepared in the comparative example. This shows that in the catalyst preparation process, the combination of pre-reduction and induced activation can promote the formation of a special catalyst structure, which has a promoting effect on the catalyst reaction activity and sulfur-resistant reaction stability.
[0159] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A sulfur-resistant Fe-based CO oxidation catalyst, characterized in that: The invention comprises a carrier and an active component supported on the carrier, wherein the active component is Fe, the carrier is at least one of alumina, titanium dioxide, ceria and zirconium dioxide, and the sulfur-resistant Fe-based CO oxidation catalyst forms a Fe / FeO x / MO x Surface-interface structure, where Fe is in a sulfur-hybridized state, FeO x is iron oxide, MO x As a carrier.
2. The sulfur-resistant Fe-based CO oxidation catalyst according to claim 1, characterized in that: Based on the total weight of the sulfur-resistant Fe-based CO oxidation catalyst, the loading amount of the active component in terms of metal element is 2-10 wt %.
3. A method for preparing a sulfur-resistant Fe-based CO oxidation catalyst, characterized in that: The method comprises the following steps: (1) impregnating the support into an aqueous solution of an iron precursor, and then drying and calcining the solution to obtain a catalyst matrix; (2) subjecting the catalyst precursor to a pre-reduction treatment in a hydrogen-containing atmosphere to obtain a catalyst intermediate; (3) inducing activation of the catalyst intermediate in an atmosphere containing CO and H2S; Wherein, the carrier is at least one of alumina, titania, cerium dioxide and zirconium dioxide.
4. The method according to claim 3, characterized in that: In step (1), the impregnation process is equal volume impregnation.
5. The method according to claim 4, characterized in that The impregnation process includes a stirring stage and a standing stage. The stirring stage lasts for 0.5-1 h, and the standing stage lasts for 6-18 h.
6. The method according to any one of claims 3 to 5, characterized in that: In step (1), the support is calcined before impregnation; Preferably, the calcination conditions of the carrier include: temperature of 400-700°C, calcination time of 4-8h; Preferably, the particle size of the carrier is 10-500 nm and the specific surface area is 60-200 m 2 / g.
7. The method according to any one of claims 3 to 5, characterized in that: In step (1), the iron precursor is at least one of iron nitrate, iron chloride and iron sulfate, preferably iron nitrate.
8. The method according to any one of claims 3 to 5, characterized in that: In step (1), during the drying process, the drying temperature is 60-90°C and the drying time is 12-24h; during the roasting process, the roasting temperature is 400-600°C, the roasting time is 3-6h, and the heating rate is 1-3°C / min.
9. The method according to claim 3, characterized in that: In step (2), the hydrogen content in the atmosphere of the pre-reduction treatment is 5-50% by volume, preferably 5-10% by volume; Preferably, the temperature of the pre-reduction treatment is 300-500°C.
10. The method according to claim 3, characterized in that: In step (3), the activation-inducing atmosphere contains CO, H2S and N2, wherein the CO content is 2-5% by volume, the H2S content is 50-200 ppm, and the N2 content is 95-98% by volume; Preferably, the activation induction temperature is 200-350°C.
11. A sulfur-resistant Fe-based CO oxidation catalyst prepared by the method according to any one of claims 3 to 10.
12. Use of the sulfur-resistant Fe-based CO oxidation catalyst according to any one of claims 1, 2 or 11 as a catalyst for carbon monoxide oxidation reaction.
13. The use according to claim 12, characterized in that: The reaction raw gas used in the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
Citation Information
Patent Citations
Preparation method and application of ZnO / CuO-CeO2 / FeSx composite catalyst for removing VOCs
CN112121823A
Catalyst for low-temperature catalytic oxidation of tail gas of Claus process and preparation method of catalyst
CN115970672A
Wide-temperature sulfur-tolerant CO oxidation catalyst as well as preparation method and application thereof
CN116237060A